2008
DOI: 10.1074/jbc.m708046200
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic Interactions of the Amyloid Precursor Protein (APP) Ectodomain Are Regulated by the Loop Region and Affect β-Secretase Cleavage of APP

Abstract: We found previously by fluorescence resonance energy transfer experiments that amyloid precursor protein (APP) homodimerizes in living cells. APP homodimerization is likely to be mediated by two sites of the ectodomain and a third site within the transmembrane sequence of APP. We have now investigated the role of the N-terminal growth factor-like domain in APP dimerization by NMR, biochemical, and cell biological approaches. Under nonreducing conditions, the N-terminal domain of APP formed SDSlabile and SDS-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 37 publications
11
97
0
Order By: Relevance
“…This points to a possible divergence in structure and function also between vertebrate and nonvertebrate APPs. Altogether, different interdomain interaction properties of distinct APP family proteins could be an explanation for functional differences of these proteins (31,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This points to a possible divergence in structure and function also between vertebrate and nonvertebrate APPs. Altogether, different interdomain interaction properties of distinct APP family proteins could be an explanation for functional differences of these proteins (31,37).…”
Section: Resultsmentioning
confidence: 99%
“…The ordered dimerization of APP has also been implicated in cell-cell interactions (29). It has been reported that dimerization depends on zinc binding (18,30), heparin binding (16), or the simultaneous interaction of several sites within the APP molecule (31) including its transmembrane domain (29) and that it is functionally associated with the concurrent dimerization of the β-site APP cleaving enzyme (28,(31)(32)(33). Recently, Gralle et al corroborated the physiological importance of APP dimerization using single molecule FRET methods (27).…”
mentioning
confidence: 99%
“…Recently, we and others have shown that APP forms dimers via at least three dimerization sites: two different sites in the ectodomain (21,22) and a third dimerization site formed by three consecutive GxxxG motifs as part of the APP-TMS (5). Here, we found that sulindac sulfide and derived compounds are able to reduce helix-helix interaction of the third dimerization site in a native bacterial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were synthesized as described previously (Beyermann et al, 1996;Kaden et al, 2008) and verified by matrix-associated laser desorption ionization-mass spectrometry (MALDI-MS; Ultraflex-II TOF/TOF, Bruker Daltonics). Briefly, peptides were synthesized at automated synthesizer (ABI 433a; Applied Biosystems) on Trt-Tentagel resin [Rapp-Polymere (0.25 mmol/g, 0.5 g) using N-(9-fluorenyl)methoxycarbonyl(Fmoc)-strategy (double couplings with 9 equivalents of Fmoc-aa/2-(1H-benzotriazole-1-yl)-1,1,3,3-tetra-methyluronium hexafluorophosphate/6 equivalents of N, N-diisopropylethylamine].…”
Section: Methodsmentioning
confidence: 99%